HUBUNGAN KUALITAS PELAYANAN KESEHATAN DENGAN KEPUASAN PASIEN BPJS KESEHATAN RAWAT JALAN HUBUNGAN KUALITAS PELAYANAN KESEHATAN DENGAN KEPUASAN PASIEN BPJS KESEHATAN RAWAT JALAN - Vebry Haryati Lubis; oom Komalasari; Vinny Maulina (Jurnal Kesehatan STIKes IMC Bintaro, 2022)
Introduction currently, BPJS service users do not only see healing, but also assess the quality of health services provided. The results of the researcher's initial survey from January to July 2020 totaled 26.839 patients consisting of 19.091 BPJS patients and 7,748 general patients, this indicates that the number of BPJS patients is more than the general patients. Research purposes: objective is to determine the relationship between the quality of health service and patient satisfaction of outpatient BPJS at IMC Bintaro Hospital. Research methodology: This research is a quantitative analytic study with a cross sectional design. The sample in this study were 58 outpatient BPJS who visited the IMC Bintaro Hospital. Data were analyzed by descriptive and bivariate analysis. Research result: The results of the univariate analysis showed that most of the respondents expressed satisfaction with service as much as 69%, with good service quality of health is 77.6%, dimensions of good physical evidence is 81.0%, good reliability is 63.8%, good response is 79.3% , good assurance is 87.9% and good empathy is 70.7%. The results of the bivariate analysis showed that there was a significant relationship between the quality of health is (p = 0,000), physical evidence is (p = 0,000), reliability is (p = 0,000), responsiveness is (p = 0.001), assurance is (p = 0.003) and empathy is (p = 0.005) with the satisfaction of outpatient BPJS. Conclusion: There’s a relationship between the quality of health service providers and the satisfaction of BPJS outpatient at IMC Bintato Hospital. BPJS outpatient have the opportunity to be satisfied with the service with an OR of 48,750.